Effects of optimizing emergency nursing care process on success rate of rescue and incidence of adverse reactions in patients with acute chest pain - Zhu, Hongyan; Ding, Dongsheng (Frontiers in Medicine, 2026)
ObjectiveTo explore the impacts of optimizing emergency nursing care process on success rate of rescue and incidence of adverse reactions in patients with acute chest pain.MethodsA total of 90 emergency patients with acute chest pain, admitted between January 2022 and December 2023, were selected as study participants. Patients were randomly assigned to either the control group or the observation group using a random number table method. The control group received routine care, while the observation group underwent an optimized emergency nursing care process. Comparisons between the two groups were made for the following outcomes: rescue and hospitalization time, rescue success rate, pain intensity, incidence of adverse reactions, mental status, and nursing satisfaction.ResultsCompared with the control group, the rescue and hospitalization time of the observation group were shorter (p < 0.01). Compared with the control group, the rescue success rate of the observation group was higher (82.22% vs. 97.78%; p = 0.013). The visual analogue score (VAS) scores of the observation group at 30 min, 60 min, 120 min and 240 min after rescue were lower than those of the control group (p < 0.01). Compared with the control group, the incidence of adverse reactions of the observation group was lower (20.00% vs. 4.44%; p = 0.024). Compared with the control group, the self-rating anxiety scale (SAS) and self-rating depression scale (SDS) scores of the observation group were lower after nursing (p < 0.01). Compared with the control group, the nursing satisfaction score of the observation group was higher (p < 0.01).ConclusionThe optimized emergency nursing care process for patients with acute chest pain is associated with relief of pain, a decrease in the occurrence of negative psychology and adverse reactions, as well as an effective improvement in the success rate of rescue.